Analisis Kebijakan Perlindungan Konsumen Keluarga dalam Pembiayaan Konsumtif di PT. Sinarmas Multifinance Cabang Cirebon Perspektif Maqashid Syariah - Youdhisthira Wibowo Andra; Wasman (Prodi Hukum Ekonomi Syariah (Muamalah), 2026)
This study aims to analyze the policies and implementation of family consumer protection in consumptive financing at PT. Sinarmas Multifinance Cirebon Branch and to evaluate them from the perspective of maqāṣid al-sharī'ah. The research employs a juridical-empirical method with a qualitative approach. Data were collected through in-depth interviews, field observations, and documentary studies, and then analyzed using both juridical and maqāṣid‑based analysis. The findings indicate that the consumer protection policies have been designed in reference to national regulations, but their implementation has not been fully optimal in protecting the interests of debtor families. From the maqāṣid perspective, the financing practices have fulfilled ḥifẓ al-māl (protection of wealth), yet remain weak in ḥifẓ al-nasl (protection of family resilience), ḥifẓ al-ʻaql (protection of rationality), ḥifẓ al-nafs (protection of psychological well‑being and dignity), and ḥifẓ al-dīn (ethical and moral responsibility). This study underscores the necessity of integrating maqāṣid values into consumer protection policies so that consumptive financing is oriented not only toward economic interests but also toward justice and family welfare.